Arginine biosynthesis in Neisseria gonorrhoeae: enzymes catalyzing the formation of ornithine and citrulline. - Shinners, E N (1978)
Many of the Neisseria gonorrhoeae strains isolated from patients require arginine for growth in a defined medium. As a basis for genetic studies of these Arg- strains, we examined two biosynthetic enzymes of Arg+ (nonrequiring) gonococci. Cell-free extracts contained (i) glutamate acetyltransferase, which catalyzes the formation of L-ornithine from alpha-N-acetyl-L-ornithine, and (ii) ornithine transcaramylase, which catalyzes the reaction between L-ornithine and carbamyl phosphate, yielding L-citrulline. Arg- strains were unable to utilze alpha-N-acetyl-L-ornithine for growth lacked significant activity of glutamate acetyltransferase, and activity was gained by Arg+ clones derived by DNA-mediated transformation. Some of the Arg- patient isolates were unable to use either alpha-N-acetyl-L-ornithine or L-ornithine in place of arginine, and two separate steps of genetic transformation were required to yield Arg+ cells. Extracts of these doubly auxotrophic cells lacked glutamate acetyltransferase activity, but, unexpectedly, they displayed normal ornithine transcarbamylase activity. This finding illustrates the importance of identifying the products specified by arg loci during genetic studies of arginine auxotrophy.